TINGKAT PENGGUNAAN DAN AKSEPTABILITAS ES KRIM YANG TERBUAT DARI TEPUNG UBI HUTAN (Dioscorea hispida dennts) - Aryo Wisatsono; Umbang Arif Rokhayati; Agus Bahar Rachman (Jurnal Ilmiah Media Agrosains, 2016)
This research aims to determine the level of provision of Ubi Hutan Powder ice cream with four treatments, that is T1=0 g, T2=90 g, T3=180 g and T4=270 g with 4 repetitions. The parameters used in this study are: (protein content, fat content). The results of chemical tests will be analyzed by the method of RAL (Rancangan Acak Lengkap), for hedonic test (texture, color, and flavor), hedonic quality (like, really like, neutral, do not like, so do not like) and the melting power analyzed descriptively. Proximate analysis test protein content is highest value at the level of use of 270 g potato flour forest that is 7,8075% and the lowest value contained in the level of provision of forest potato flour 0 g namely 6,91% for the highest fat content found in the level of provision of forest potato flour 270 g namely 7,74% and the lowest value contained in the level of provision of forest potato flour 0 g is 6,16%. From the data obtained for the hedonic quality most preferred that the level of provision of forest potato flour T4=6,68% and the least preferred by the panelists at the level of the provision of Ubi Hutan Powder T2=5,20. The conclusion showed that the manufacture of ice cream Ubi Hutan Powder significant effect on protein and very significant effect on fat content.